2007
DOI: 10.1111/j.1600-0633.2007.00267.x
|View full text |Cite
|
Sign up to set email alerts
|

Temperature‐mediated en route migration mortality and travel rates of endangered Snake River sockeye salmon

Abstract: Temperature-mediated en route migration mortality and travel rates of endangered Snake River sockeye salmon Keefer ML, Peery CA, Heinrich MJ. Temperature-mediated en route migration mortality and travel rates of endangered Snake River sockeye salmon.Abstract -Conservation efforts for endangered Snake River sockeye salmon (Oncorhynchus nerka) have been hindered by high en route adult mortality during their 1450 km freshwater spawning migration. Identifying causal factors for this mortality has been difficult gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
134
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(140 citation statements)
references
References 35 publications
4
134
2
Order By: Relevance
“…Several anadromous salmon species that return to spawn each year in this region do so during the summer period when average temperatures and seasonal extremes (i.e., MaxWATs) are warming most rapidly. In some instances, these migrations are now periodically disrupted during especially warm periods as the fish pause to congregate near coldwater sources (Goneia et al 2006;Sutton et al 2007;Keefer et al 2009) and fish that migrate during the year's warmest temperatures often return less successfully to their spawning areas (Cooke et al 2004;Keefer et al 2008). Thermal "events" wherein hundreds or thousands of adult salmon die simultaneously because thermal tolerances are exceeded have been documented in recent years (Lynch andRisley 2003, Doremus andTarlock 2008;Keefer et al 2010) and important recreational fisheries are now sometimes suspended during warm periods to minimize additional fish stress (Brick et al 2008).…”
Section: Implications For Salmonid Fishesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several anadromous salmon species that return to spawn each year in this region do so during the summer period when average temperatures and seasonal extremes (i.e., MaxWATs) are warming most rapidly. In some instances, these migrations are now periodically disrupted during especially warm periods as the fish pause to congregate near coldwater sources (Goneia et al 2006;Sutton et al 2007;Keefer et al 2009) and fish that migrate during the year's warmest temperatures often return less successfully to their spawning areas (Cooke et al 2004;Keefer et al 2008). Thermal "events" wherein hundreds or thousands of adult salmon die simultaneously because thermal tolerances are exceeded have been documented in recent years (Lynch andRisley 2003, Doremus andTarlock 2008;Keefer et al 2010) and important recreational fisheries are now sometimes suspended during warm periods to minimize additional fish stress (Brick et al 2008).…”
Section: Implications For Salmonid Fishesmentioning
confidence: 99%
“…Accelerated egg development could benefit populations in high elevation streams that are currently too cold and unproductive to support populations (Bystrom et al 2006;Coleman and Fausch 2007) but in other streams could desynchronize juvenile hatching and emergence dates from optimal periods dictated by annual floods and food availability (Brannon et al 2004). In a few instances, migration dates of salmon past hydroelectric dams in northwest U.S. rivers appear already to be shifting in response to warming temperatures (Keefer et al 2008;Crozier et al 2008) but data to describe long-term biological responses during other life-stages or across spatial distributions are rare.…”
Section: Implications For Salmonid Fishesmentioning
confidence: 99%
“…provide an excellent system for understanding the effects of climate change on fishes; their anadromous life history exposes them to pressures found in both freshwater and marine environments, whereas their ecological, economic and cultural value make their long-term viability a chief concern among stakeholders. Anomalously high river temperatures have recently been identified as a significant cause of mortality in Pacific salmon populations at both the juvenile [21] and adult stage [22]. Indeed, a collapse of aerobic scope has been empirically linked to high mortality during spawning migrations of sockeye (Oncorhynchus nerka) salmon [20].…”
Section: Introductionmentioning
confidence: 99%
“…dams, generating stations) and operations can interrupt a river's natural flow regime, fish habitat, and system connectivity, and thus has the potential to negatively influence the upstream migration of fish, particularly anadromous fish such as salmonids that must travel upriver to natal spawning grounds (Poff et al 1997, Enders et al 2009). Recent studies have demonstrated delays (Thorstad et al 2003, Keefer et al 2004, 2008, Pon et al 2009a or failure of mature adult salmon to reach spawning grounds (e.g. Gowans et al 2003, Thorstad et al 2003 and higher energetic costs for salmonids exposed to variable water flows (Murchie & Smokorowski 2004, Tiffan et al 2010 in regulated rivers.…”
Section: Introductionmentioning
confidence: 99%